2018
DOI: 10.1002/job.2320
|View full text |Cite
|
Sign up to set email alerts
|

Family‐supportive supervisor behaviors: A review and recommendations for research and practice

Abstract: Family-supportive supervisors empathize with employees' attempts to balance work and nonwork, while also actively facilitating employees' ability to manage work and nonwork demands. Over the last three decades, approximately 60 publications have investigated family-supportive supervisor behavior (FSSB), with one third of these appearing in just the last 3 years. Thus, as the burgeoning FSSB literature continues to develop, there is a critical need to understand this body of work in totality in order to further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
178
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(199 citation statements)
references
References 92 publications
(305 reference statements)
18
178
0
3
Order By: Relevance
“…First of all, our findings demonstrate that the presence of a supportive and resourceful work environment (POS) enables FSSBs, while time pressure and negative consequences of using work-family initiatives prevent the display of FSSBs (Bakker & Demerouti, 2003;Bakker & Sanz-Vergel, 2013). This finding deepens our knowledge of the antecedents of FSSBs (Crain & Stevens, 2018) and addresses the lack of empirical evidence particularly from an organizational culture perspective . Understanding what drives FSSBs is crucial in the light of the evidence that they constitute practical and relatively lesscostly interventions that organizations can capture to drive the subordinates' functioning at work (Kossek et al, 2017;Bond et al, 2006;Burch et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…First of all, our findings demonstrate that the presence of a supportive and resourceful work environment (POS) enables FSSBs, while time pressure and negative consequences of using work-family initiatives prevent the display of FSSBs (Bakker & Demerouti, 2003;Bakker & Sanz-Vergel, 2013). This finding deepens our knowledge of the antecedents of FSSBs (Crain & Stevens, 2018) and addresses the lack of empirical evidence particularly from an organizational culture perspective . Understanding what drives FSSBs is crucial in the light of the evidence that they constitute practical and relatively lesscostly interventions that organizations can capture to drive the subordinates' functioning at work (Kossek et al, 2017;Bond et al, 2006;Burch et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…In a growing field of research, studies have mainly focused on the consequences of FSSBs, overlooking the question of what drives supervisors to engage in these behaviors (Crain & Stevens, 2018). Among the few studies that explored the triggers of FSSBs, a predominant focus has been on the characteristics of supervisors (e.g., workaholism, LMX) who engage in FSSBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that various family-speci c support systems, such as family friendly organizational policies and climate can reduce WPC (76). A growing body of research has investigated family-supportive supervisors, i.e., supervisors at work who promote the management of work and non-work responsibilities and acknowledge their employees private life (77,78). Facilitating family-supportive supervisors through training might be an effective approach to improve employee work, family, and health outcomes (77).…”
Section: Discussionmentioning
confidence: 99%
“…Although Chinese researchers have begun to pay attention to this field, the relevant research is not much. Although a few studies have shown that family supportive working environment can affect employees' attitudes and behaviors such as job satisfaction, job engagement, turnover tendency and job performance [8]. However, few studies have explored the influence of FSSB on employees' extra-role behaviors in the workplace.…”
Section: Introductionmentioning
confidence: 99%